Attributable risk and economic cost of hospital admissions for mental disorders due to PM2.5 in Beijing - Wu, Ziting; Chen, Xi; Li, Guoxing; Tian, Lin; Wang, Zhan; Xiong, Xiuqin; Yang, Chuan; Zhou, Zijun; Pan, Xiaochuan (The Science of the total environment, 2020)
Few studies have estimated the attributable risk and economic cost of mental disorders (MDs) due to particulate matters with aerodynamic diameter of <2.5 μm (PM2.5) exposure in Beijing. This study aims to identify the possible correlation between PM2.5 and risk of hospital admissions (HAs) for MDs in Beijing and calculate the attributable risk and economic cost. A generalized additive model (GAM) with controlling for time trend, meteorological conditions, holidays and day of the week was used to estimate the associations. Stratified analyses were performed by age, gender and season. We further estimated the health and economic burden of HAs for MDs attributable to PM2.5. A total of 17,252 HAs for MDs were collected. A 10 μg/m3 daily increase in PM2.5 was associated with a statistically significant risk increase of 3.55% for HAs for MDs. The effects of PM2.5 exposures on HAs for MDs were more pronounced in males, elderly (≥65 years old) individuals and in cold seasons. Using WHO's air quality guidelines as the reference, 15.12% of HAs and 16.19% of the related medical expenses for MDs were attributed to PM2.5 during the study period. PM2.5 accounts for substantial morbidity and economic burden of MDs for both the society and households, which shows environmental protections are essential to improve mental health status of the population. [Display omitted] •One of the first study to estimate the economic costs of MDs due to PM2.5.•A city-wide representative dataset with accurate medical expenses was used.•Increased risk of HAs due to MDs associated with PM2.5.•16% of the total medical expenses for MDs were attributed to PM2.5.•The total medical expenses and out-of-pocket cost caused by PM2.5 were estimated.